Does EIF2S3 Retrogene Activation Regulate Cancer/Testis Antigen Expression in Human Cancers? - Rohozinski, Jan; Edwards, Creighton L. (Frontiers in Oncology, 2020)
Cancer/Testis (C/T) antigens are a group of antigens, expressed in almost all types of cancers, which can elicit an immune response in patients whose cancers express these antigens. They are currently of great interest as targets for the development of cancer biomarkers and the creation of immunotherapies that directly target tumors in patients. Currently there are 280 C/T antigens and their variants listed on the CT antigen data base. All known C/T antigens are encoded for by genes which are normally only expressed in the male testis; specifically during the process of spermatogenesis. They are therefore only expressed in germ cells that are in the process of differentiating into sperm. Expression of C/T antigens in tumors is thus a biological anomaly as, with the exception of germ cell tumors, cancers arise from somatic tissues which are not known to express any of the genes specifically involved in spermatogenesis. How and why C/T antigens are expressed in tumors remains an enigma. In this paper we present a hypothesis which proposes a mechanism for the activation of C/T antigen encoding genes in tumors. We propose that aberrant activation of the human autosomal gene, EIF2S3B, which regulates initiation and maintenance of spermatogenesis in males, is responsible for C/T expression. Because both male and females have tumors that express C/T antigens activation of spermatogenesis genes in tumors must involve a non-sex specific pathway. This can be explained by the copy number of EIF2S3 genes uniquely present within the human genome